I-PASS Mentored Implementation Handoff Curriculum: Frontline Provider Training Materials - O'Toole, Jennifer K. (MedEdPORTAL, 2020)
INTRODUCTION: The I-PASS Handoff Program is a comprehensive handoff curriculum that has been shown to decrease rates of medical errors and adverse events during patient handoffs. Frontline providers are the key individuals participating in handoffs of patient care. It is important they receive robust handoff training. METHODS: The I-PASS Mentored Implementation Handoff Curriculum frontline provider training materials were created as part of the original I-PASS Study and adapted for the Society of Hospital Medicine (SHM) I-PASS Mentored Implementation Program. The adapted materials embrace a flipped classroom approach with an emphasis on adult learning theory principles. The training includes an overview of I-PASS handoff techniques, TeamSTEPPS team communication strategies, verbal handoff simulation scenarios, and a printed handoff document exercise. RESULTS: As part of the SHM I-PASS Mentored Implementation Program, 2,735 frontline providers were trained at 32 study sites (16 adult and 16 pediatric) across North America. At the end of their training, 1,762 frontline providers completed the workshop evaluation form (64% response rate). After receiving the training, over 90% agreed/strongly agreed that they were able to distinguish a good- from a poor-quality handoff, articulate the elements of the I-PASS mnemonic, construct a high-quality patient summary, advocate for an appropriate environment for handoffs, and participate in handoff simulations. Universally, the training provided them with knowledge and skills relevant to their patient care activities. DISCUSSION: The I-PASS frontline training materials were rated highly by those trained and are an integral part of a successful I-PASS Handoff Program implementation.